Does magnetic resonance imaging increase core body temperature in children? Results of the administration of propofol and ketofol: a randomized clinical study - Beyoğlu, Çiğdem Akyol; Kendigelen, Pınar; Beyoğlu, İlhan; Altındaş, Fatiş; Kuruoğlu, Sebuh; Kaya, Güner (The Turkish Journal of Pediatrics, 2020)
Background and Objectives. Magnetic resonance imaging (MRI) may cause a temperature increase in the imaging area, while intravenous anesthetics may develop a tendency for hypothermia, especially in the pediatric population. The effect of different anesthetics on core body temperature in children during these procedures remains controversial. We examined the effect of propofol and ketofol on core body temperatures in a pediatric population during MRI. Our hypothesis was that the increase in body temperature will be more prominent in pediatric patients receiving ketofol than in those receiving propofol. Methods. This was a randomized, prospective, double-blind study in pediatric patients aged 6 months to 10 years. The patients were American Society of Anesthesiologist (ASA) physical class I-II who had undergone MRI under anesthesia at the Cerrahpasa School of Medicine, MRI Area, between August 2014 and February 2016. Patients were assigned to one of two groups: Group I (propofol group) and Group II (ketofol group). MRIs were performed with a 1.5 Tesla (T) device. Bilateral tympanic membrane temperature measurements before and after the procedure were performed. Results. Body temperature decreased in both groups after MRI. Clinically significant hypothermia or hyperthermia was not observed in any of the patients. Conclusion. Temperature monitoring is not necessary for every patient being imaged. However, temperature changes should be closely monitored in high-risk patients.
Keywords: body temperature; ketofol; magnetic resonance imaging; propofol; sedation